Optimization of throughput performance for low-power VLSI interconnects. - Deodhar, V.V (IEEE Transactions on VLSI systems)
The technique of optimal voltage scaling and repeater insertion is analyzed in this paper to reduce power dissipation on global interconnects. An analytical model for the maximum bit-rate of a very large scale integration interconnect with repeaters has been derived and results are compared with HSPICE simulations. The analytical model is also used to study the effects of interconnect length and scaling on throughput. The throughput-per-bit-energy is analyzed to determine an optimum combination of supply voltage and repeaters for a low-power global interconnect with 250 nm × 250 nm cross-sectional dimensions implemented with the 180 nm micro-optical silicon system technology node. It is shown that the optimal supply voltage is approximately equal to twice the threshold voltage. A case study illustrates that a combination of 1 V supply along with one repeater per millimeter increases the throughput-per-bit-energy to over three times that of a latency-centric interconnect of 2 V, which results in a 70% reduction in power dissipation without any loss of throughput performance.